How to make money with ISO 9000 a guide to profitable quality management - Highlands, James (McGraw-Hill, 1999)
The ISO 9000 quality management system is the worldwide standard for improved product quality and customer satisfaction through improved business processes. The Big 3 auto makers, NASA, and thousands of other organizations have developed ISO 9000 systems and received ISO 9000 accreditation. Yet, most companies are at a loss as to how to make the most of their ISO 9000 systems because, there are no practical guides to maximizing them, until now. Written by a renowned ISO 9000 trainer and consultant, this is the first and only comprehensive guide to achieving tangible bottom-line results with ISO 9000. Readers get detailed, step-by-step instructions on how to put ISO 9000 quality standards to work at every organizational level for increased profits and market share.